1892
DOI: 10.1144/gsl.jgs.1892.048.01-04.17
|View full text |Cite
|
Sign up to set email alerts
|

The Olenellus Zone in the North-west Highlands of Scotland

Abstract: While tracing the various subdivisions of the Durness Series of quartzites and limestones from Sutherland southwards into Rossshire, careful attention has been paid to any indications of fossiliferous zones which might throw additional light on the age of the strata. During last season's campaign, certain sections in the Dundonnell Forest happily furnished the evidence which has been eagerly sought after. Physical Features of the Dundonnell Forest. Between Little Loeir Broom and Loeh Maree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The area is structurally overlain by the ductile (~ amphibolite-facies) Sgurr Beag Thrust (Tanner 1971;Roberts et al 1987). To the west, the Caledonian Foreland and the Moine Thrust Zone in the footwall of the Moine Thrust contains a tripartite sequence comprising Archaean gneiss basement (the Lewisian Gneiss Complex); Meso-to Neoproterozoic siliciclastic sedimentary rocks (the Stoer, Sleat and Torridon groups); and a Cambro-Ordovician sedimentary succession (Peach et al 1907;Park et al 2002;Stewart 2002;Kinnaird et al 2007). The Moine Thrust Zone on the Isle of Skye, west of Knoydart, is dominated by Sleat and Torridon group strata folded in the large-scale recumbent Lochalsh Syncline (e.g.…”
Section: Geological Setting Of Knoydart Peninsulamentioning
confidence: 99%
See 1 more Smart Citation
“…The area is structurally overlain by the ductile (~ amphibolite-facies) Sgurr Beag Thrust (Tanner 1971;Roberts et al 1987). To the west, the Caledonian Foreland and the Moine Thrust Zone in the footwall of the Moine Thrust contains a tripartite sequence comprising Archaean gneiss basement (the Lewisian Gneiss Complex); Meso-to Neoproterozoic siliciclastic sedimentary rocks (the Stoer, Sleat and Torridon groups); and a Cambro-Ordovician sedimentary succession (Peach et al 1907;Park et al 2002;Stewart 2002;Kinnaird et al 2007). The Moine Thrust Zone on the Isle of Skye, west of Knoydart, is dominated by Sleat and Torridon group strata folded in the large-scale recumbent Lochalsh Syncline (e.g.…”
Section: Geological Setting Of Knoydart Peninsulamentioning
confidence: 99%
“…Stratigraphic correlations between Moine and Torridonian rocks on either side of the Moine Thrust have been suggested for a long time (Peach et al 1907;Peach and Horne 1930;Kennedy 1951;Sutton & Watson, 1964;Johnstone et al 1969;Nicholson 1993;Prave 1999) but have remained somewhat controversial (Clough in Peach et al 1910;Gibbons and Harris 1994;Stewart 2002;Friend et al2003;Cawood et al 2004). Krabbendam et al (2008) demonstrated that the lower Morar Group and Torridon Group in Ross-shire and Sutherland can be correlated on the basis of similar sedimentology, stratigraphy, detrital zircon ages and…”
Section: Stratigraphic Correlation Across the Moine Thrustmentioning
confidence: 99%
“…The combination of high precipitation with a lack of vegetation has no parallels in modern-day orogens, so it is difficult to judge how much greater associated rates of erosion would have been, but it is likely that they were very high. The distribution of detritus derived from the Grenville orogen across Laurentia (Rainbird et al 1992;Banks et al 2007;Cawood et al 2007;Petterson et al 2009) Peach et al 1907;Kennedy 1951;Sutton & Watson 1964;Stewart 2002;Friend et al 2003), although it has often been discounted because of the potentially large displacements that may have occurred on the intervening Moine Thrust. Krabbendam et al (2008) have shown that the Altnaharra Formation and the Torridon Group are similar in terms of their age of deposition, fluvial sedimentology, stratigraphical thickness and position on Lewisian basement, geochemistry, detrital zircon age pattern, and overall sediment transport direction (see also Rainbird et al 2001;Kinnaird et al 2007).…”
Section: Allen and Allen 2005)mentioning
confidence: 99%
“…Farther north in Assynt, where the Pipe Rock member is more widespread (Peach et al, 1907;British Geological Survey, 2007), Skolithos pipe-shaped trace fossils still form 'dimples' on striated surfaces, constraining abrasion to a few millimetres. Subaerial surface weathering of quartzite proceeds exceedingly slowly, and the preservation potential of striae is much higher than that of any other rocks in the region (e.g., Lawson, 1996).…”
Section: Glacial Erosional Landformsmentioning
confidence: 99%